PERAN PAJAK BUMI DAN BANGUNAN UNTUK MENINGKATKAN PENDAPATAN DAERAH - Widayanti Widayanti (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
axes are a very important source of state revenue for the implementation of national development, improving people's welfare. Determination of the imposition of Land and Building Tax on tax objects used by the state to manage, is regulated by Government Regulation. The land and building tax has been made so fairly by the government, but in reality it is felt to be unfair by the community because Land and Building Tax is an objective tax that does not view the socio-economic conditions or the ability of the community as taxpayers. The United Nations Division for the central government and regional governments has been regulated in Law No. 32 of 2004 concerning Regional Government as amended by Law No. 8 of 2005 concerning the implementation of Perpu No. 3 of 2005 concerning Regional Government into Law - 10% for Central Government 90% for Local Government.